2012
DOI: 10.1080/09654313.2012.709064
|View full text |Cite
|
Sign up to set email alerts
|

Doing R&D or Not (in a Crisis), That Is the Question …

Abstract: This study investigates how corporate R&D evolves in the light of the contemporary economic crisis. We study empirical evidence from past downturns, discuss the relevant literature and perform an empirical analysis of recent business survey data (collected during 2009). Pivotal for our considerations is the question whether companies tend to spend more or less on R&D and innovation activities during periods of recession. We empirically analyse what general patterns can be distinguished in this regard, given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
2
28
0
4
Order By: Relevance
“…R&D expenditure of the business sector distinctly fell in 2008 and 2009 (and also in next years, see OECD 2012). As Cincera et al (2012) note, businesses usually decrease the amount they spend on R&D during economic crisis as a cost-reduction strategy in time of economic pressure and tight credit constraints, the similar development was reported also in some countries in the sample. Based on the presented data it can be concluded that higher education R&D expenditure influences economic growth diversely -in the pre-crisis period negatively, in the post-crisis period positively.…”
Section: Discussionmentioning
confidence: 93%
“…R&D expenditure of the business sector distinctly fell in 2008 and 2009 (and also in next years, see OECD 2012). As Cincera et al (2012) note, businesses usually decrease the amount they spend on R&D during economic crisis as a cost-reduction strategy in time of economic pressure and tight credit constraints, the similar development was reported also in some countries in the sample. Based on the presented data it can be concluded that higher education R&D expenditure influences economic growth diversely -in the pre-crisis period negatively, in the post-crisis period positively.…”
Section: Discussionmentioning
confidence: 93%
“…More recently the OECD (2009) has made it clear that private investments in innovation are mainly procyclical and decrease significantly during economic downturns. In the same vein, Archibugi and colleagues Filippetti and Archibugi, 2011;Archibugi et al, 2013) have found evidence to support the notion that the 2008-2009 global crisis has negatively affected European companies' investment in innovation and reduced aggregate private investments in R&D. However some other evidence (Cincera et al, 2012) suggests the existence of different types of company responses, including a group of firms that increase their R&D investments in years of crisis with the expectation of gathering the benefits of the upswing to come. Similar types of findings are available for firms in Latin American countries (Paunov, 2012) or in Eastern Europe (Correa and Iootty, 2011).…”
Section: Previous Studiesmentioning
confidence: 85%
“…The empirical evidence of how the economic crisis is related to innovative investments is mostly supporting the procyclical arguments (Archibugi et al 2013a(Archibugi et al , 2013bCincera et al 2012;Laperche et al 2011;Madrid-Guijarro et al 2013;OECD 2009;Paunov 2012). Some of these scholars have explored the characteristics of firms that have increased their innovative investments during the crisis, showing that recessions do not hit all firms equally and that some strategies could help to face a turbulent climate.…”
Section: Introductionmentioning
confidence: 92%
“…Within this scenario, cooperation in innovation activities -which is one of the means the firms use to purse innovation (Tether 2002) -could either become less important for achieving innovation performance during the crisis or alternatively could offer new opportunities to cope with the challenges of the crisis. While several studies have investigated the relations between economic crises and R&D expenditures (Archibugi et al 2013a(Archibugi et al , 2013bCincera et al 2012) or innovation output (Madrid-Guijarro et al 2013), little is known about how the crisis has affected cooperation in innovation activities and its relationship with innovation performance.…”
Section: Introductionmentioning
confidence: 99%